The production of recombinant cationic α‐helical antimicrobial peptides in plant cells induces the formation of protein bodies derived from the endoplasmic reticulum. Issue 1 (17th September 2013) - Company, Nuri; Nadal, Anna; La Paz, José‐Luis; Martínez, Sílvia; Rasche, Stefan; Schillberg, Stefan; Montesinos, Emilio; Pla, Maria
Summary Synthetic linear antimicrobial peptides with cationic α‐helical structures, such as BP100, are valuable as novel therapeutics and preservatives. However, they tend to be toxic when expressed at high levels as recombinant peptides in plants, and they can be difficult to detect and isolate from complex plant tissues because they are strongly cationic and display low extinction coefficient and extremely limited immunogenicity. We therefore expressed BP100 with a C‐terminal tag which preserved its antimicrobial activity and demonstrated significant accumulation in plant cells. We used a fluorescent tag to trace BP100 following transiently expression in Nicotiana benthamiana leaves and showed that it accumulated in large vesicles derived from the endoplasmic reticulum (ER) along with typical ER luminal proteins. Interestingly, the formation of these vesicles was induced by BP100. Similar vesicles formed in stably transformed Arabidopsis thaliana seedlings, but the recombinant peptide was toxic to the host during latter developmental stages. This was avoided by selecting active BP100 derivatives based on their low haemolytic activity even though the selected peptides remained toxic to plant cells when applied exogenously at high doses. Using this strategy, we generated transgenic rice lines producing active BP100 derivatives with a yield of up to 0.5% total soluble protein.